2005
DOI: 10.2320/matertrans.46.251
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Size Strengthening in Equal-Channel-Angular-Pressing Processed AZ31 Mg Alloys with a Constant Texture

Abstract: The effects of ECAP temperature and post-ECAP annealing on grain size, texture and mechanical behavior have been examined. The softening of ECAPed Mg alloys despite the considerable grain size refinement has been ascribed to the texture change during ECAP. The strength of the ECAPed AZ31 Mg alloys, however, increased with decrease in grain size following the standard Hall-Petch relation when the similar texture could be retained. Based on the present analysis, it could be concluded that it was practically hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 16 publications
5
44
0
1
Order By: Relevance
“…This is because besides the grain size, the mechanical properties can also be possibly influenced by the crystallographic texture. 25,26) Previous studies have suggested that most of the basal planes are inclined to be 45 from the extrusion direction along the shear plane below processing temperature of 523 K while tend to be parallel to the extrusion direction above 573 K. 27) This formation of 45 angle below 523 K causes the basal planes to slip easier due to the maximum imposed shear force, which as a result, retards the increase of strength originated from the largely decreased grain size at 523 K. 28) Further, by comparing our data with available reports, we found that our yield stress of 192 MPa at 523 K is larger than that of 160 MPa 29) and 130 MPa 30) obtained by 6 repetitive ECAEs, and that of 160 Mpa 24) by the hot extrusion. Additionally, the UCS of 386 MPa and compressive ratio of 14.4% at 523 K are also comparable to corresponding values of 370 MPa and 15% for the hot-extruded AZ31.…”
Section: )supporting
confidence: 47%
“…This is because besides the grain size, the mechanical properties can also be possibly influenced by the crystallographic texture. 25,26) Previous studies have suggested that most of the basal planes are inclined to be 45 from the extrusion direction along the shear plane below processing temperature of 523 K while tend to be parallel to the extrusion direction above 573 K. 27) This formation of 45 angle below 523 K causes the basal planes to slip easier due to the maximum imposed shear force, which as a result, retards the increase of strength originated from the largely decreased grain size at 523 K. 28) Further, by comparing our data with available reports, we found that our yield stress of 192 MPa at 523 K is larger than that of 160 MPa 29) and 130 MPa 30) obtained by 6 repetitive ECAEs, and that of 160 Mpa 24) by the hot extrusion. Additionally, the UCS of 386 MPa and compressive ratio of 14.4% at 523 K are also comparable to corresponding values of 370 MPa and 15% for the hot-extruded AZ31.…”
Section: )supporting
confidence: 47%
“…It has been reported that Mg alloys processed by equal channel angular processing or hot rolling for grain refinement exhibit not only higher yield stresses but larger elongations at room temperature (32)(33)(34). However, conflicting results have also been reported mainly due to the texture characteristics and complication of deformation twinning (35,36). By eliminating the complicating effects of grain boundaries and compatibility from neighboring grain orientations, our in situ TEM experiments revealed the intrinsic size dependence of plastic anisotropy and offered clear evidence that it is indeed possible to achieve both high strength and high ductility by tuning the external dimensions of the sample.…”
Section: Discussionmentioning
confidence: 84%
“…In Mg alloys, for instance, the AZ31 alloy [46], the texture even takes the dominant position in strengthening contributions to the yield strength (see Ref [47,54] for more examples). Consequently, Mg samples with a strong texture can show significant hardness anisotropy, as was revealed for our samples in Fig.…”
Section: Anisotropic Hardness and Strength Of Mgmentioning
confidence: 99%